Judicial Amendment of the Contract - Al-Ajili, Lafta (Journal of Legal Sciences, 2025)
be proven, as man is a social being who cannot live alone, and therefore there is no dispute about his inability to meet his needs by himself. This exchange of benefits takes place through a legal means called (contract). Everything we obtain today of basic needs for the purpose of securing living, housing, trade and exchanging experiences is done through one path, which is the agreement that may be made between its parties directly or through an intermediary.Contracts differ in terms of importance. What we derive from the contract through meeting our simple needs does not raise any problems, and we do not suffer from the difference in the circumstances in which it arose, considering that its implementation takes place at a single moment in time.However, large and continuously implemented contracts, which may take a long time to achieve the interests of their parties, may be subject to some force majeure circumstances that were not expected to occur, and none of them prepared themselves to confront them and adapt to them, which puts them in front of a huge and burdensome loss, which necessitates restoring the economic balance of the contract.Restoring the economic balance of the contract should not be left to the will of its parties, but rather the judiciary should undertake this by granting it discretionary authority in light of which it moves to reduce the severity of the burden that has been inflicted on the debtor, even if not completely, but in the manner that he can bear under normal. Manner that he can bear under normal circumstancesAccepting this intervention was not easy in light of the dominance of the principles of the authority of the will and the binding force of the contract, as the convergence of the two wills on the establishment of the contract was considered a law that must be respected, and no amendments to it were made regardless of the circumstances facing its contracting parties. However, social, economic and political developments did not take long to change this firm conviction of the strength of the will and its opposition to any amendment to the contract. Legislation responded to the principle of the judge's intervention in restoring the economic balance of the contract if its parties faced exceptional circumstances that made the implementation of the contract burdensome for the debtor and he faced a huge loss as a result. Or if the agreed compensation estimated by the contract.ting parties was exorbitant, or if the contract included arbitrary conditions that the weak party in it could not bear, which necessitated the intervention of the judiciary to amend or exempt from them.